Quality control of digital representations of manuscript texts: proposal of a standards-based method - Arillo Jesús Robledano (De Gruyter, 2021)
This study aims to propose a quality control method for digitized versions of manuscript documents that will be relevant for paleographical and codicological analysis. The methodology applied consisted of a systematic review of papers related to automated analysis of the physical characteristics of handwritings and document supports in the field of digital paleography, as well as of the numerous standards that have been emerging in the field of image engineering for quality assessment in digital image recordings. We also worked with a sample of 275 digital representations of pages or double pages of manuscript documentation dating to between the 12th and 17th centuries. As a result of this study, we propose a taxonomy of physical attributes of the handwritings and of their documentary supports that must be represented in the digital image with a high level of fidelity and without any distortions that could lead scholars to erroneous interpretations of the physical and formal characteristics of the original documents. On the basis of this taxonomy, we identified a set of typical distortions caused by digitization processes that can affect the recording quality of the physical attributes previously proposed, as well as a set of parameters and metrics for measuring quality that can be used to create a sufficiently exhaustive quality model. We also detected a series of limitations which, if not properly managed, can compromise the effectiveness of these types of controls.